Assessing the Impact of Power Outages on Appliances of Farmers and Fisherfolks in Selected Barangays of Cawayan, Masbate, Philippines: Basis for a Proposed Extension Program - Ibañez, Roger; Velza, Jacob Frederick; Luzong, Alberto (Romblon State University Research Journal, 2024)
This paper presents data on the economic background and power supply situation in selected barangays of the Municipality of Cawayan in Masbate, Philippines. It examined the constraints in power supply experienced by the respondents. The study results showed that many respondents had an annual income of less than ₱18,200, which was considered low and may have resulted in difficulty in paying high bills brought by power outages. All respondents relied on the power grid as their source of electricity, and power interruptions were a common occurrence. The data revealed that 97.7% of respondents experienced power interruptions, with 51.1% experiencing 3-4 hours of interruption. Almost all respondents claimed that power interruption increased their electric consumption and bill, and 56% were not satisfied with their electric bill when there was a power interruption. The study also found that refrigerators and televisions were the most power-consuming appliances, and bulbs were reported to be the most affected by power interruption. Possible reasons for power interruptions cited by respondents included part of the service and performing maintenance. The study findings suggested a need for capacity training for farmers and fishers on adopting solar energy to address power supply constraints. The extension project proposal titled, Electrical and Electronic Designs using Renewable Energy that Led to Net Zero, was an excellent opportunity to provide training to all marginalized sectors in the municipality of Cawayan. The proposal included training on solar installation and maintenance.